Sistem Pengambilan Keputusan Kelayakan Pemberian Bantuan Rumah Layak Huni dengan Metode SAW - Aranski, Alvendo Wahyu; Yunaldi, Andri (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The house is a basic part that must be fulfilled in carrying out daily life. Currently, the government has provided housing assistance that is unfit for habitation to become a suitable home for residents in Indonesia to obtain comfort and peace for people who cannot afford to repair their homes due to economic deficiencies. Provision of Livable housing assistance has conditions that have been set by the government. The provision of housing assistance is very helpful for residents who have inadequate housing to get a better and more suitable home to live in. The problem in this study lies in an imperfect system or a system that is still manual in selecting residents who are entitled to assistance in repairing houses to make them more habitable. The benefit of this research is to help the government in selecting people who are entitled to receive livable housing assistance in accordance with applicable regulations. The method that is suitable for resolving cases of providing livable housing assistance is the Simple Additive Weighting (SAW) method, this method provides alternatives and criteria in election, so that later the final results of the highest value criteria can be seen for those who are entitled to a livable house provided by the government. Four criteria are used as the basis for providing assistance, namely the condition of the house, income, employment and dependents. The people who are most deserving of being given a livable aid house in the name of Masdianti with a final score of 0.9055. The decision support system can be used as a problem solving system for providing livable assistance to poor people.